Non-adiabatic flow characteristics of micro impeller - Qianwei Sun; Qiushi Li; Ali Arshad; Zhiping Li (Propulsion and Power Research, 2014)
Non-adiabatic working condition is one of the major causes of performance deterioration in micro gas turbine engines. Complex micro scale geometry, low Reynolds number operating condition and high surface to volume ratio all lead to severe heat transfer. This paper first established a simple heat transfer model to determine appropriate non-adiabatic boundary condition for computational fluid dynamics (CFD) simulations. Isothermal wall temperature is identified as a heat transfer boundary based on model analysis in combination with material selection for pre-design of the engine and verified by the experiment carried out on directed structure applied in the model. A series of numerical simulations with adiabatic and non-adiabatic boundary conditions is then carried out to study the flow characteristics of high speed, low Reynolds number micro impeller. The physical nature for significant performance degradation related to flow behavior changes due to heat transfer effect is revealed by detailed analysis of typical flow features extracted from the comparative investigation. The result established the basis for heat transfer modeling of micro impeller purposing implications for design modification in order to attain high efficiency and better performance.